Perancangan Sistem Presensi Berbasis Pengenalan Wajah Guna Mencegah Pemalsuan Data Kehadiran Siswa - Tasya Nurul Hidayah; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Attendance is an activity used to collect attendance data for students or employees in an institution. Currently the use of the presence system is still using the conventional method. Along with the development of information technology, at this time the presence system has begun to develop, for example, the presence using fingerprints (fingerprint), from the fingerprint presence system can be developed again into facial recognition (face recognition), in order to prevent things that cannot be done with a fingerprint presence. The method proposed to develop a face recognition-based presence system is the waterfal method, because the waterfal method has successive stages starting from analysis, design, implementation, testing, and maintenance. The results of the face recognition based presence system research are: With the help of this facial recognitionbased presence website, the presence cannot be faked anymore, because the photos that can be uploaded on the web are only the same photos as those registered in the database, With this facial recognition-based attendance website, attendance cannot be faked and can increase student productivity, Students who do not attend on time at the time of admission will be considered absent and will be subject to sanctions so that later they feel deterred and do not do it the next day, unless there is a reason to make them late for attendance.